Salt tolerance evaluation and mini-core collection development in Miscanthus sacchariflorus and M. lutarioriparius - Tang, Yanmei; Li, Shicheng; Zerpa-Catanho, Dessireé; Zhang, Zhihai; Yang, Sai; Zheng, Xuying; Xue, Shuai; Kuang, Xianyan; Liu, Mingxi; He, Xiong; Yi, Zili; Xiao, Liang (Frontiers in Plant Science, 2024)
Marginal lands, such as those with saline soils, have potential as alternative resources for cultivating dedicated biomass crops used in the production of renewable energy and chemicals. Optimum utilization of marginal lands can not only alleviate the competition for arable land use with primary food crops, but also contribute to bioenergy products and soil improvement. Miscanthus sacchariflorus and M. lutarioriparius are prominent perennial plants suitable for sustainable bioenergy production in saline soils. However, their responses to salt stress remain largely unexplored. In this study, we utilized 318 genotypes of M. sacchariflorus and M. lutarioriparius to assess their salt tolerance levels under 150 mM NaCl using 14 traits, and subsequently established a mini-core elite collection for salt tolerance. Our results revealed substantial variation in salt tolerance among the evaluated genotypes. Salt-tolerant genotypes exhibited significantly lower Na + content, and K + content was positively correlated with Na + content. Interestingly, a few genotypes with higher Na + levels in shoots showed improved shoot growth characteristics. This observation suggests that M. sacchariflorus and M. lutarioriparius adapt to salt stress by regulating ion homeostasis, primarily through enhanced K + uptake, shoot Na + exclusion, and Na + sequestration in shoot vacuoles. To evaluate salt tolerance comprehensively, we developed an assessment value (D value) based on the membership function values of the 14 traits. We identified three highly salt-tolerant, 50 salt-tolerant, 127 moderately salttolerant, 117 salt-sensitive, and 21 highly salt-sensitive genotypes at the seedling stage by employing the D value. A mathematical evaluation model for salt tolerance was established for M. sacchariflorus and M. lutarioriparius at the seedling stage. Notably, the mini-core collection containing 64 genotypes developed using the Core Hunter algorithm effectively represented the overall variability of the entire collection. This mini-core collection serves as a valuable gene pool for future in-depth investigations of salt tolerance mechanisms in Miscanthus.